The influence of brand image and product quality on purchasing decisions in Medan Perjuangan District - Zebua, Adiwima; Lbn. Raja, Togu Harlen; Sinurat, Riomas; Zebua, Mardianus (Jurnal Mantik, 2024)
This research was carried out to determine the influence of brand image and product quality on the purchase decision of Honda Beat in Medan Perjuangan District. This study uses a qualitative method and uses a questionnaire as a data collection tool. The data of this research that became the population were people in the Medan Perjuangan sub-district who used Honda Beat motorcycles. The sampling technique uses random sampling samples from the community in the Medan Pejuangan sub-district of as many as 92 people. The data analysis technique uses a validation test, reliability test, classical assumption test, multiple linear regression test, t-test, f test, and determination coefficient test (R^2), using the SPSS version 16 application. The results of the study showed that the results of the t-test of the brand image variable (X_1) t calculated at 2.786 > the table t of 1.986, then the brand image variable (X_1) had an influence and significance on the purchase decision (Y) of Honda Beat in Medan Perjuangan District.  The results of the t-test of the product quality variable (X_2) t calculated as 6.054 > t the table of 1.986, the product quality variable (X_2) has an influence and significance on the purchase decision (Y) in Medan Perjuangan district. From the results of the study, it can be concluded that the result of the F test of 54.503 > the F table of 3.10 can be concluded that the brand image (X_1) and product quality (X_2) together (simultaneously) have a significant influence on the purchase decision (Y). The result of determination (R^2) was 54.0%. while the remaining 46.0% was explained by other variables that were not studied